Peran DP3AP2KB Terhadap Pencegahan Pergaulan Bebas Remaja Di Kota Batam Tahun 2021 - Sutarto, Dendi; Sulistyaningsih, Dewi; Roselina Efendi, Winda (Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to determine the role of the Department of Women's Empowerment, Child Protection, Population Control and Family Planning (DP3AP2KB) in preventing cases of promiscuity in Batam City in 2021. This research is research that uses qualitative research. The informants in this research were the Head of Family Prosperity and Family Empowerment (KSPK) DP3AP2KB, Ambassadors and Members of the Batam Genre, Teenagers who are classified as promiscuous, and Parents of Teenagers in the city of Batam. Data was collected using a semi-structured interview method. The results of this research state that DP3AP2KB has played a positive role in preventing promiscuity in Batam City. Continuous efforts need to be made to increase youth participation, improve program success, and respond to field constraints more effectively in order to achieve the desired results in protecting adolescents from promiscuity. .